Characterization of caves as bat roosts in the brazilian-paranense biogeographic region of Bolivia - Lizarro, Dennis; Aguirre, Luis F.; Pérez-Zubieta, José Carlos; Vargas, Aideé; Galarza, M. Isabel (THERYA, 2020)
Bats play vital roles in nature as pollinators, seed dispersers, and natural controllers of insect pests. They serve as indicators of habitat disturbance and provide an insight into the health status of an ecosystem. This enormous importance contrasts with the lack of information on the current state of their roosts in Bolivia, particularly as regards caves and caverns. A search for caves and caverns was carried out in the eastern department of Santa Cruz, Bolivia, corresponding to the Brazilian-Paranense biogeographic region. Subsequently, an environmental-structural characterization of the caves was conducted to obtain biological information by capturing and identifying bats in eastern Bolivia. Interspecific associations in caves and the relationship between roost characteristics and bat diversity were explored and described based on the variables evaluated. A total of 19 caves were evaluated. A correlation between environmental and structural parameters was investigated, showing a relationship between cave length and humidity. Seven species of cave bats were identified, and two species of threatened Bolivian bats (Lonchorhina aurita and Natalus macrourus) were found in four caves. The caves evaluated are new records of this vital habitat for bats in the country. The presence or absence of bat species was found to depend on the structural characteristics of the cave (length, complexity), but not on temperature, although humidity may play a role in the presence of species. Among the species found, those highly specialized in the selection and use of roosts at caves could be prone to local extinctions. It is suggested that further investigations should be carried out on the ecology of these cave-dwelling bat species to identify the roosting patterns of bats and their distribution range, to elaborate conservation and management programs for caves and the animal communities sheltered.